Melatonin enhances the efficacy of anti-PD-L1 by improving hypoxia in residual tumors after insufficient radiofrequency ablation - Yanqiao Ren; Licheng Zhu; Yusheng Guo; Jinqiang Ma; Lian Yang; Chuansheng Zheng; Xiangjun Dong (Elsevier, 2024)
The hypoxic microenvironment and inflammatory state of residual tumors caused by insufficient radiofrequency ablation (iRFA) are major reasons for rapid tumor progression and pose challenges for immunotherapy. We retrospectively analyzed the clinical data of patients with hepatocellular carcinoma (HCC) treated with RFA and observed that iRFA was associated with poor survival outcomes and progression-free survival. Using an orthotopic HCC mouse model and a colorectal liver metastasis model, we observed that treatment with melatonin after iRFA reduced tumor growth and metastasis and achieved the best outcomes when combined with anti-programmed death-ligand 1 (anti-PD-L1) therapy. In mechanism, melatonin inhibited the expression of epithelial-mesenchymal transitions, hypoxia-inducible factor (HIF)-1α, and PD-L1 in tumor cells after iRFA. Flow cytometry revealed that melatonin reduced the proportion of myeloid-derived suppressor cells and increased the proportion of CD8+ T cells. Transcriptomic analysis revealed an upregulation of immune-activated function-related genes in residual tumors. These findings demonstrated that melatonin can reverse hypoxia and iRFA-induced inflammation, thereby overcoming the immunosuppressive tumor microenvironment (TME) and enhancing the efficacy of immunotherapy.